How Can Teachers Tailor Success? Innovative Strategies for Content, Process, and Product in EFL Classrooms - Suryati, Imas; Koesoemo Ratih; Maryadi (Universitas Hamzanwadi, 2024)
This study aimed to examine the Implementation of differentiated instruction in an EFL classroom, focusing on content, process, and product dimensions. It involved an English teacher and thirty-nine 8th-grade students at a junior high school. The research sought to identify the teacher's strategies to implement differentiated instruction, guided by Tomlinson's (2001) theory of Differentiated Instruction. Using a descriptive-qualitative methodology, the study employed interviews, observations, and document analysis as data collection instruments. The findings indicate that the teacher employed diverse texts and resources alongside varied support systems to differentiate content. For process differentiation, strategies included multiple intelligences and flexible grouping. Differentiation of the product involved varied questioning techniques, leading to activities such as student worksheets, group tasks, and presentations. This research contributes to understanding differentiated instruction in Indonesian EFL classrooms, highlighting the challenges and suggesting the need for further innovation in instructional strategies. Despite difficulties, the study illustrates the teacher's efforts to incorporate various differentiated instruction strategies, underscoring the potential for enhancing EFL teaching practices.